Web Based Information System of Food Plant Commodities in Serdang Bedagai District by Using PHP and MYSQL - Jhon Erikson Tarigan; Achwil Putra Munir; Saipul Bahri Daulay (Universitas Sumatera Utara, 2013)
Food corps information system in Serdang Bedagai Regency are still stored in books and/or files that arevery limited in effectiveness. Computerized information delivery methods and internet networks are solutionsthat are worth to try to overcome the problems of information flow. Study was designed to produce systemsthat can help process the delivering, storing, and monitoring of data displayed in a web form. The systemswere designed in a user oriented programming language PHP, and MySQL database web Apachewebserver. This system could improve efficiency and effectiveness of information flow, especially food corpsinformation. The results showed that the distribution and types of food corps commodities in each district inSerdang Bedagai Regency was different. The spread and the kind depend on topographic, the price leveland market demand in the area.